Sarapul Ascension Brotherhood and Its Activities in the Late XIX - Early XX Centuries - M. Yu. Polovnikova (Научный диалог)
The article raises the question of the implementation of religious policy within the borders of the Vyatka province in the second half of the 19th century in terms of creating religious educational organizations to increase the effectiveness of the clergy with the Old Believer and non-Orthodox populations. Based on archival documents and published sources, the history of the foundation and the main activities of the Ascension Brotherhood on the territory of the Sarapul Vicariate, created to conduct religious and educational work among the local population and provide assistance to other religious organizations of the Vyatka diocese, are examined. The novelty of the study is that a comprehensive review of the history and activities of the Ascension Brotherhood, opened in Sarapul in 1892, is carried out for the first time. The author dwells on the religious and educational work of the Ascension Brotherhood, which was his main business. It is reported that members of the fraternity, with the assistance of the local clergy, engaged in religious-educational readings and conversations, which were popular with the local population. It is noted that this activity was initially supported by the local authorities of Sarapul, but over time, assistance to the Ascension Brotherhood from the local secular authorities became minimal. It turned out that members of the Ascension Brotherhood and the organizers of the readings were forced to continue their activities at the expense of material assistance from donors and support from the clergy of the Vyatka diocese.